2022
DOI: 10.5423/ppj.oa.12.2021.0176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Properties of Lichen Substances against Plant Pathogens

Abstract: Plant pathogens pose major threats on agriculture and horticulture, causing significant economic loss worldwide. Due to the continuous and excessive use of synthetic pesticides, emergence of pesticide resistant pathogens has become more frequent. Thus, there is a growing needs for environmentally-friendly and selective antimicrobial agents with a novel mode of action, which may be used in combination with conventional pesticides to delay development of pesticide resistance. In this study, we evaluated the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The minimum bactericidal concentration (MBC) of the three kinds of nanoparticles was 1.56 μg/mL, which was much lower than that of thiodiazole copper (MBC > 100 μg/mL, Figure S4 ). Compared with the antibiotics [ 51 ], natural compounds [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and synthetic compounds [ 18 , 19 , 20 , 21 , 22 , 23 ] reported in the literature, copper-based nanoparticles also have advantages in bactericidal performance. The antibacterial mechanism of copper-based nanoparticles may be related to their compositions, morphologies, and sizes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum bactericidal concentration (MBC) of the three kinds of nanoparticles was 1.56 μg/mL, which was much lower than that of thiodiazole copper (MBC > 100 μg/mL, Figure S4 ). Compared with the antibiotics [ 51 ], natural compounds [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and synthetic compounds [ 18 , 19 , 20 , 21 , 22 , 23 ] reported in the literature, copper-based nanoparticles also have advantages in bactericidal performance. The antibacterial mechanism of copper-based nanoparticles may be related to their compositions, morphologies, and sizes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many novel compounds or methods have been developed to control kiwifruit bacterial canker, including natural products [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], synthetic organic compounds [ 3 , 18 , 19 , 20 , 21 , 22 , 23 ], copper complexes [ 24 , 25 ], sulfur [ 26 ], bacteriophages [ 27 , 28 , 29 ], and other biological control agents [ 30 , 31 ]. These methods exhibited excellent control efficacies for kiwifruit bacterial canker.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they also have the potential to impact the spatial partitioning of microrganisms in a microbial consortium. The induced fungal compound lecanoric acid has been found to specifically inhibit the growth of the plant-pathogenic basidiomycete Rhizoctonia solani ( 37 ). These compounds suggest a possible mechanism by which certain microorganisms are included in and excluded from a microbial consortium (Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…17−19 Notwithstanding, the precise mechanism underpinning Usnic acid's antifungal prowess remains elusive. 17 Significantly, Usnic acid has been identified as a natural product inhibitor that selectively targets Arabidopsis thaliana 4-hydroxyphenylpyruvate dioxygenase (AtHPPD), evincing pronounced inhibitory potency, as substantiated in previous reports. 20,21 Inspired by former studies, we reasoned that the primary antifungal mechanism of Usnic acid may be associated with inhibition of HPPD given its stringent conservation across prokaryotes and eukaryotes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, a C-terminal α helix makes the cavity show different states, which may impact on the entry of the inhibitors and thus influence the species selectivity. 34 Although Usnic acid's antimicrobial activities have been documented, [16][17][18]36 the intricate antimicrobial mechanism remains elusive. Here, our results suggested that (+)-Usnic acid displayed antifungal activities against plant pathogenic fungi [Sclerotinia sclerotiorum (Ss).…”
Section: ■ Introductionmentioning
confidence: 99%